Data on an Austrian Company's Productivity in the Pre-Covid-19 Era, During the Lockdown and After Its Easing: To Work Remotely or Not? - Beno, Michal; Hvorecky, Jozef (Frontiers in Communication, 2021)
The Covid-19 crisis across the world has increased the proportion of e-working. The transition from cubicles to the home office raised many questions in connection with companies adopting the new working conditions. Our paper provides recent evidence on the extent of this move, its impact on workplace evolution, productivity and the future prevalence of the face-to-display workplace after the easing of the lockdown. It uses data from 154 service employees of an Austrian sports and leisure product company obtained using online surveys on employees' opinions on e-working. By a coincidence, we conducted the first of them shortly prior to the epidemic. We decided to modify our planned research goals and decided to study their opinions during different Covid-19 stages. As a result, our findings do not follow all the academic standards. First, they are almost impossible to replicate due to the specific coincidence. Then, the shift in our aims leads us to minor changes in the content of the questionnaire. There are not only significant differences in the proportion of workers in the office and at home during the different periods of the lockdown. After its end, there was a significant increase in the number of those who had started working at home—more than one half. Compared to the period prior to the lockdown, they have a tolerant attitude to their work from home and believe that their productivity might remain the same. For many of them the change was an unavoidable obligation so they would prefer to return to the traditional workplace. The results suggest that more than one fifth want to continue working from home permanently, about one third more frequently than before, more than a quarter sometimes and just one seventh not at all. We studied the issues related to their productivity and its limits during all three stages. There are three important reasons for the fall in productivity related to e-working: (1) Providing childcare/home schooling, pet sitting and/or care for others while working (>one-fourth); (2) Work-from-home routine (>one-fourth); and (3) Having less work to do (>one-fifth).